2020
DOI: 10.1101/2020.08.03.235465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KDM4 Orchestrates Epigenomic Remodeling of Senescent Cells and Potentiates the Senescence-Associated Secretory Phenotype

Abstract: Cellular senescence restrains the expansion of neoplastic cells through several layers of regulation, including epigenetic decoration of chromatin structure and functional modulation of bioactive components. Here we report that expression of the histone H3-specific demethylase KDM4 is upregulated in human stromal cells upon cellular senescence. In clinical oncology, upregulated KDM4 and diminished H3K9/H3K36 methylation are correlated with adverse survival of cancer patients post-chemotherapy. Global chromatin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…1F, 2G). When we treated cells on a 2D stiff substate with a KDM4 inhibitor, ML324 44 , during the expansion process, we found that chromatin architecture (H3K9me3 foci, nuclear area) changed significantly in comparison to the vehicle control (DMSO) cells (Fig. 4B,C,D), yet the nuclear aspect ratio did not change significantly compared to DMSO controls (Fig.…”
Section: Demethylase Inhibition Partially Restores Both Chondrogenic H3k9me3 Chromatin Architecture and Gene Expression Following Expansimentioning
confidence: 96%
“…1F, 2G). When we treated cells on a 2D stiff substate with a KDM4 inhibitor, ML324 44 , during the expansion process, we found that chromatin architecture (H3K9me3 foci, nuclear area) changed significantly in comparison to the vehicle control (DMSO) cells (Fig. 4B,C,D), yet the nuclear aspect ratio did not change significantly compared to DMSO controls (Fig.…”
Section: Demethylase Inhibition Partially Restores Both Chondrogenic H3k9me3 Chromatin Architecture and Gene Expression Following Expansimentioning
confidence: 96%
“…Consistent with the heterogeneity of SCAPs across different senescent cell types, senescent human fat cell progenitors (preadipocytes or mesenchymal stromal cells) are sensitive to D but not Q or F, while senescent human umbilical vein endothelial cells are sensitive to Q or F but not D 14 . Since the first SCAPs were discovered, others have been identified and, based on 31,48,60,63,64,103,157,[214][215][216][217][218] . the various forms of the SASP can comprise chemokines, extracellular matrix proteases, remodeling factors, bioactive lipids, noncoding nucleotides and reactive metabolites 7,31,[59][60][61][62][63][64] .…”
Section: Discovery and Development Of Senolytic Drugsmentioning
confidence: 99%
“…the SASP is a key feature of cellular senescence. Cellular stressors induce DNA damage response signaling, which activates key transcription factors and pathways including NF-κB, CCAAt/enhancer binding protein-β (C/EBPβ), GAtA binding protein 4 (GAtA4), p38 and JAK-StAt, which can drive and modulate the SASP31,48,60,63,64,103,157,[214][215][216][217][218] . the various forms of the SASP can comprise chemokines, extracellular matrix proteases, remodeling factors, bioactive lipids, noncoding nucleotides and reactive metabolites7,31,[59][60][61][62][63][64] .…”
mentioning
confidence: 99%
“…Given that eliminating senescent cells by senolytics can cause unwanted side effects and that the detrimental effects of senescent cells are largely mediated by the SASP, an alternative approach to targeting senescent cells is to develop senomorphics. Senomorphic drugs, such as BET inhibitor I‐BET‐762 and histone lysine demethylase subfamily 4 (KDM4) inhibitor ML324, aim to suppress the SASP [55,56]. Notably, senomorphics are expected not to affect the arrest of cell growth that is associated with senescence [57].…”
Section: Targeting the Sasp With Senomorphicsmentioning
confidence: 99%
“…Furthermore, inhibition of the epigenetic regulator Bromodomain Containing 4 (BRD4), which helps to organize new super enhancers to drive the SASP, suppresses this secretory phenotype [55]. Similarly, a potent inhibitor that selectively targets KDM4 can also reduce SASP gene expression by altering the accessibility of chromatin and the transcriptomic landscape [56]. Importantly, the inhibition of these chromatin modifiers reduces SASP gene expression without altering the growth arrest of senescent cells, which provides a promising avenue for being targeted in the therapeutic context.…”
Section: Targeting the Sasp With Senomorphicsmentioning
confidence: 99%